Assembling Amperometric Biosensors for Clinical Diagnostics - María Soledad Belluzo; María Elida Ribone; Claudia Marina Lagier (Sensors, 2008)
Clinical diagnosis and disease prevention routinely require the assessment ofspecies determined by chemical analysis. Biosensor technology offers several benefits overconventional diagnostic analysis. They include simplicity of use, specificity for the targetanalyte, speed to arise to a result, capability for continuous monitoring and multiplexing,together with the potentiality of coupling to low-cost, portable instrumentation. This workfocuses on the basic lines of decisions when designing electron-transfer-based biosensorsfor clinical analysis, with emphasis on the strategies currently used to improve the deviceperformance, the present status of amperometric electrodes for biomedicine, and the trendsand challenges envisaged for the near future.